2018
DOI: 10.5539/gjhs.v10n2p134
|View full text |Cite
|
Sign up to set email alerts
|

Is Smartphone Addiction Associated with a Younger Age at First Use in University Students?

Abstract: Background: Recent evidence highlighted the potential of habitual smartphone use among youth to become an addiction analogous to established behavioral and substance-related addictions. While investigators revealed independent predictive effects of several sociodemographic factors, personality traits, psychological conditions, and smartphone usage patterns on smartphone addiction (SPA) in university students, none examined the independent effect of age at first smartphone use, a potential predictor variable, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
(38 reference statements)
2
6
0
1
Order By: Relevance
“…A recent review found that problematic internet use is most common in adolescents, as they are more vulnerable to internet addiction due to their limited ability to control their enthusiasm for internet activities [ 10 ]. Moreover, first using a smartphone at a younger age was found to be significantly associated with several smartphone addiction symptoms [ 28 ]. Following this, the initial use of the internet and smartphones was added to our survey.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review found that problematic internet use is most common in adolescents, as they are more vulnerable to internet addiction due to their limited ability to control their enthusiasm for internet activities [ 10 ]. Moreover, first using a smartphone at a younger age was found to be significantly associated with several smartphone addiction symptoms [ 28 ]. Following this, the initial use of the internet and smartphones was added to our survey.…”
Section: Methodsmentioning
confidence: 99%
“…Following this, the initial use of the internet and smartphones was added to our survey. In addition, participants answered questions related to gaming patterns based on a study on internet-based games that determined game play as an important indicator of the potential risk of internet gaming addiction [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Young people are highly involved with their smartphones and feel valued and accepted by others which may heighten their self-esteem (Walsh et al , 2010; Zulkefly and Baharudin, 2009). Higher smartphone addiction score has been observed among those who owned first smartphone at a young age (Jaalouk and Boumosleh, 2018). It was observed that as people grow old, they spend less time on the smartphone because of the decrease in the social usage and social stress, and increase in self-control, thus the chances of them getting addicted to their smartphone is low (Haug et al , 2015; Van Deursen et al , 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Experts-whether pediatricians, psychologists, education specialists, or social scientists specialized in communication-tend not to give clear answers to this question, and it is generally left to parents to establish when their children are capable of autonomously managing a media device. Indeed, little evidence has been published on the drivers of the age of smartphone acquisition or on the short-and long-term consequences of early ownership: while some studies have found a negative relationship between early access and school performance or well-being (Dempsey et al, 2019;Jaalouk & Boumosleh, 2018), other research shows that early owners have higher information and communications technology (ICT) self-efficacy (Li et al, 2023).…”
Section: Introductionmentioning
confidence: 99%